Transnational perspectives on innovation in teaching and learning technologies - Jean-François, Emmanuel, 1971- (Brill Sense, 2018)
This volume highlights patterns with transnational applications or facets that are nationally/culturally situated. The chapters provide insights on strategies and technologies for teaching and learning that are being used across the world in various unique national/cultural contexts. The perspectives reflect innovations in teaching and learning from Africa, Asia and the Middle East, Europe, Latin America, and North America. Topics covered include: transnational innovative teaching, innovative learning technologies, electronic portfolio and self-directed learning, on-line teaching and learning in in-service teacher education, dual language learner, outcome-based education, E-learning and simulation, democratic assessment, deliberative dialoguing as a teaching/learning strategy, and smart glasses digital strategy for learning.